The Effect of Current Ratio, Debt to Equity Ratio and Total Asset Turnover on Return on Equity (Manufacturing Industry Companies in the Consumer Goods Sector Food and Beverage Sub-sector Listed on the Indonesia Stock Exchange for the Period 2013-2020) - Neneng Khoiriah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio and Total Asset Turnover on Return on Equity in manufacturing companies on the Indonesia Stock Exchange in the food and beverage subsector. Data collection is done by collecting secondary data in the form of financial statements of 6 companies for the period 2013-2020, the method of determining the sample used is the purposive sampling method in which the financial statements are made up of panel data and processed with Eviews 9 software. The results of this study show that the Current ratio (X1) is not significant effect on Return on Equity (Y). Where the results of the t arithmetic test are smaller than the t table (-0.931024 < 2.01537) with a significance value of 0.3567 > 0.05 then Ho is accepted and H1 is rejected. Debt to Equity Ratio (X2) has a significant effect on Return on Equity (Y). Where the test results t arithmetic is greater than t table (2.475227 > 2.01537) with a significance value of 0.0171 < 0.05 then Ho is rejected and H1 is accepted. Total Asset Turnover (X3) has a significant effect on Return on Equity (Y). t count is greater than t table (2.819950 > 2.01537) with a significance value of 0.0071 < 0.05, so Ho is rejected and H1 is accepted. Current Ratio (X1), Debt to Equty Ratio (X2) and Total Asset Turnover (X3) simultaneously have a significant and significant effect on the Return on Equity (Y) variable. where the results of the calculated F test are greater than F table 4.652487 > 3.21 and are also shown by the probability value being smaller than the significant level (0.006555 < 0.05), so Ho is rejected and H1 is accepted.